Question 12 - Properties of Determinant - Chapter 4 Class 12 Determinants
Last updated at April 16, 2024 by Teachoo
Properties of Determinant
Question 2 Important Deleted for CBSE Board 2025 Exams
Question 3 Deleted for CBSE Board 2025 Exams
Question 4 Deleted for CBSE Board 2025 Exams
Question 5 Important Deleted for CBSE Board 2025 Exams
Question 6 Important Deleted for CBSE Board 2025 Exams
Question 7 Important Deleted for CBSE Board 2025 Exams
Question 8 (i) Important Deleted for CBSE Board 2025 Exams
Question 8 (ii) Deleted for CBSE Board 2025 Exams
Question 9 Important Deleted for CBSE Board 2025 Exams
Question 10 (i) Deleted for CBSE Board 2025 Exams
Question 10 (ii) Important Deleted for CBSE Board 2025 Exams
Question 11 (i) Deleted for CBSE Board 2025 Exams
Question 11 (ii) Important Deleted for CBSE Board 2025 Exams
Question 12 Important Deleted for CBSE Board 2025 Exams You are here
Question 13 Important Deleted for CBSE Board 2025 Exams
Question 14 Important Deleted for CBSE Board 2025 Exams
Question 15 (MCQ) Important Deleted for CBSE Board 2025 Exams
Question 16 (MCQ) Deleted for CBSE Board 2025 Exams
Properties of Determinant
Last updated at April 16, 2024 by Teachoo
Question 12 By using properties of determinants, show that: |■8(1&x&x2@x2&1&x@x&x2&1)| = (1 – x3)2 Solving L.H.S |■8(1&x&x2@x2&1&x@x&x2&1)| Applying R1 → R1 + R2 + R3 = |■8(𝟏+𝐱𝟐+𝐱&𝐱+𝟏+𝐱𝟐&𝐱𝟐+𝐱+𝟏@x2&1&x@x&x2&1)| Taking (1 + x + x2) Common from 1st row = (𝟏+𝐱+𝐱𝟐) |■8(1&1&1@x2&1&x@x&x2&1)| Applying C1 → C1 − C2 = (1+x+x2) |■8(𝟏−𝟏&1&1@x2−1&1&x@x−x2&x2&1)| = (1+x+x2) |■8(0&1&1@x2−1&1&x@x(1−x)&x2&1)| = (1+x+x2) |■8(𝟎&1&1@(𝐱−𝟏)(𝑥+1)&1&x@−x (𝐱−𝟏)&x2&1)| Taking (x – 1) common from C1 = (x – 1) (1+x+x2) |■8(0&1&1@(x+1)&1&x@−x&x2&1)| Applying C2 → C2 − C3 = (x – 1) (1+x+x2) |■8(0&𝟏−𝟏&1@x+1&1−x&x@−x&x2−1&1)| = (x – 1) (1+x+x2) |■8(0&𝟎&1@x+1&−(𝒙−𝟏)&x@−x&(x+1)(𝐱−𝟏)&1)| Taking (x – 1) common from 2nd Column = (x – 1) (1+x+x2) (x – 1) |■8(0&0&1@x+1&−1&x@−x&𝑥+1&1)| = (x – 1)2 (1+x+x2) |■8(0&0&1@x+1&−1&x@−x&𝑥+1&1)| Expanding Determinant along R1 = (x – 1)2 (1+x+x2) ( 0|■8(−1&𝑥@𝑥+1&1)|−0|■8(𝑥+1&x@−𝑥&1)|+1|■8(𝑥+1&−1@−x&𝑥+1)|) = (x – 1)2 (1+x+x2) ( 0−0+1|■8(𝑥+1&−1@−x&𝑥+1)|) = (x – 1)2 (1+x+x2) (0−0+1((𝑥+1)2−𝑥)) = (x – 1)2 (1+x+x2) ((𝑥+1)^2−𝑥) = (x – 1)2 (1 + x + x2) ((x2 + 1 + 2x) – x) = (x – 1)2 (1 + x + x2) (1 + x + x2) = (x – 1)2 (1 + x + x2)2 = ((x – 1) (1 + x + x2))2 = (– (1 – x) (1 + x + x2))2 = ((1 – x) (1 + x + x2))2 = (13 – x3)2 = (1 – x3)2 = R.H.S Hence proved = (x – 1)2 (1 + x + x2)2 = ((x – 1) (1 + x + x2))2 = (– (1 – x) (1 + x + x2))2 = ((1 – x) (1 + x + x2))2 = (13 – x3)2 = (1 – x3)2 = R.H.S Hence proved We know that a3 – b3 = (a – b)(a2 + b2 + ab) Here, a = 1 , b = x